Me and white supremacy : combat racism, change the world, and become a good ancestor - Saad, Layla F (Sourcebooks, 2020)
"When Layla Saad began an Instagram challenge called #meandwhitesupremacy, she never predicted it would become a cultural movement. She encouraged people to own up and share their racist behaviors, big and small. She was looking for truth, and she got it... Thousands of people participated in the challenge, and over 80,000 people downloaded the supporting work Me and White Supremacy. Updated and expanded from the original edition, Me and White Supremacy teaches readers how to dismantle the privilege within themselves so that they can stop (often unconsciously) inflicting damage on people of color, and in turn, help other white people do better, too"--